FARMER EMPOWERMENT IN REDUCING EXPOSURE AND RESIDUAL PESTICIDES IN VEGETABLES: A CROSS SECTIONAL STUDY AT KUTAI KARTANEGARA DISTRICT, INDONESIA - Ryan Ningsih; Ratih Wirapuspita (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Based on the success of a pesticide in to overcome the problem of pest attacks, more farmers tend to use pesticide in higherdoze. Aims: The purpose of this research is to identify problems and looking for cause a problem so that obtained alternative problem handling food safety in products of vegetable planted farmers. Methods: An observational study with cross sectional design. The total sample of 25 farmers with non-random sampling technique that is total population. Analysis of the data used univariate and bivariate analysis using Spearman correlation test and continued with a linear regression test Results: All respondents in plant vegetable use pesticides.A kind of pesticides most commonly used is the type a fungicide.Doses pesticides used use a unit of cover pesticide per tank. one cropping the average 14 times at least 4 times and most widely 34 cases direction spraying done farmers most 96 % in line with the direction of the wind nutritional status of respondents most normal 64 % knowledge was 76 % knowledgeable either by rerata 90,72 attitude respondents 52 % be negative and rerata a score 84,24 .The majority of respondents in spraying 96 % used apersonal protective equipment ( PPE ) . PPE who rarely used the eyes of glass and a mitt tangan.seluruh respondents have not yet undergone poisoning pesticide because the an enzyme cholinestrase 87.5 - 100 % in the category of normal and 8 % of respondents decreasing levels of an enzyme of cholinesterase be 87.5 % Conclusion: There was the influenced of knowledge of respondents to a decrease in levels of enzymes cholinestrase. Need to be conducted socialization / pesticide management training good and true should socialization and assistance to farmers on management of the purchase of pesticides, pengaplikasian , storage and disposal need to be managed and in continuous observation .